Comparative impact of logistics performance index, ease of doing business and logistics cost on economic development: a fuzzy QCA analysis - Saini, Mohan; Hrušecká, Denisa (Journal of Business Economics and Management, 2021)
This research papers aims to evaluate the impact of two major institutional indexes logistics performance index (LPI) and ease of doing business (EODB) along with logistics cost (LC) on the economic development (Gross domestic product – GDP per capita). The variables selected for the research study provides the comprehensive impact and forms the core of the economy for any country. Top seven economies of the world (China, France, Germany, India, Japan, United Kingdom and USA) along with Czech Republic, Singapore and Slovenia have been selected for this analysis. Mid-sized Economies of Czech Republic, Singapore, Slovenia have been selected for the regional balance of Asia and Europe and for cooperative results. A preliminary analysis of Pearson correlation analysis and detailed fuzzy qualitative comparative analysis have been opted for the study. The results illustrate that LPI is the core component for displaying the positive results on economic development. LC and EODB have displayed mixed results and will be studied in future research for identifying their impact on economic development. Future research will incorporate indexes such as global competitive index, innovation index for the evaluation of the combined impact on economic development.